2011
DOI: 10.1088/1748-6041/6/3/035003
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of thermal calcination and an alkaline hydrolysis method in the isolation of hydroxyapatite from Thunnus obesus bone

Abstract: In the present study, hydroxyapatite (HAp) was isolated from Thunnus obesus bone using alkaline hydrolysis and thermal calcination methods. The obtained ceramic has been characterized by thermal gravimetric analysis (TGA), Fourier transform infrared spectroscopy (FT-IR), powder x-ray diffraction analysis (XRD), field-emission scanning electron microscopy, energy-dispersive x-ray analysis, transmission electron microscopy (TEM), selected area diffraction analysis, cytotoxic analysis and cell proliferation analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
53
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 41 publications
10
53
0
1
Order By: Relevance
“…The peaks corresponding to carbonate ions in the crystal lattice (about 850 and 860 cm −1 ) are not detected in the spectra; this is due to the thermal treatment of the samples at high temperatures, causing carbonate to be released in gaseous form. This is in agreement with what was observed for other samples made from animal bones [26].…”
Section: Annealing Of the Bonessupporting
confidence: 93%
See 1 more Smart Citation
“…The peaks corresponding to carbonate ions in the crystal lattice (about 850 and 860 cm −1 ) are not detected in the spectra; this is due to the thermal treatment of the samples at high temperatures, causing carbonate to be released in gaseous form. This is in agreement with what was observed for other samples made from animal bones [26].…”
Section: Annealing Of the Bonessupporting
confidence: 93%
“…As such, there is no apparent degree of orientation within the material, but the rounded grains appear to be undergoing sintering at 1000°C, as the necking and the fusing of grains can also be observed. Other authors have reported that the presence of chloride ions in ceramic precursors can delay crystallisation and sintering until higher-than-usual temperatures [26,27]. The existence of only one type of grain agrees with the XRD data suggesting this sample is pure HAp.…”
Section: Treatment With Ca-containing Solutionssupporting
confidence: 86%
“…The sharp peaks at 1409 cm −1 are assigned to the CH 3 symmetrical deformation mode and 1074 cm −1 and 1031 cm −1 correspond to indicate the C O stretching vibrations (C O C). As evidenced by IR spectra of HAp, characteristic absorption bands of natural HAp are observed and compared with the previous reports [29,30]. Large number of bands appeared in the HAp spectra (3571, 1459, 1415, 1089, 1050, 962, 633, 603 and 571 cm −1 ) that were similar to HAp reference spectrum close to earlier data [29,40].…”
Section: Stretching Frequency Of Scaffoldssupporting
confidence: 85%
“…In chitosan scaffold, three main peaks were observed at 10.5, 20.0 (maximum intensity) and 22.5. The diffraction pattern of HAp is already reported extensively elsewhere [29,30]. Broad diffraction bands similar to chitosan scaffold were observed for CS and AP due to amorphous nature of the polysaccharides.…”
Section: X-ray Diffraction Studiessupporting
confidence: 59%
See 1 more Smart Citation